1998
DOI: 10.1116/1.590056
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and calculations of the valence band offsets of SiOx/ZnS(111) and SiOx/CdTe(111) heterojunctions

Abstract: SiO x (x>1.5) overlayers have been in situ grown on ZnS (111) and CdTe (111) substrates. Synchrotron radiation photoemission spectroscopy has been used to measure the electronic structures and band lineups of these two heterojunctions. The valence band offsets of SiOx/ZnS(111) and SiOx/CdTe(111) derived from the measurements are 2.8±0.2 and 4.7±0.2 eV, respectively. Harrison’s “tight binding” theory is extended into the theoretical estimation of the band lineups of SiO2 related heterojunctions. The agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…SiO 2 was used as the coating material because of its favorable band alignment when forming a heterojunction with ZnS. 4 Furthermore, SiO 2 , which consists of light elements and has low density, exhibits minimal losses in electron penetration and has a penetration depth nearly twice as large as ZnS. In the CRT manufacturing process, SiO 2 coating of ZnS phosphors is routinely performed to improve dispersion and adhesion properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SiO 2 was used as the coating material because of its favorable band alignment when forming a heterojunction with ZnS. 4 Furthermore, SiO 2 , which consists of light elements and has low density, exhibits minimal losses in electron penetration and has a penetration depth nearly twice as large as ZnS. In the CRT manufacturing process, SiO 2 coating of ZnS phosphors is routinely performed to improve dispersion and adhesion properties.…”
mentioning
confidence: 99%
“…Ban et al showed that SiO 2 forms a heterojunction with ZnS with nearly equal conduction band and valence band offsets of 2.4 and 2.8 eV, respectively. 4 The wide band gap SiO 2 layer with a positive conduction band offset relative to ZnS is then expected to reflect the electrons generated by the incident electron beam from the defective high surface recombination velocity region back into the phosphor. It is also possible that the SiO 2 could passivate surface recombination centers.…”
mentioning
confidence: 99%